Pengaruh After Sales Service Dan Peran Customer Experience Terhadap Kepuasan Pelanggan Jaringan Internet Indotranshome Pada PT. Indotrans Data Cibinong Bogor - Muhammad Fadliyanto; Dewi Ningsih (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of After Sales Service and Customer Experience on the level of customer satisfaction of Indotranshome internet services at PT. Indotrans Data. The study uses a quantitative approach with a population of Indotranshome customers and involves 87 respondents as samples. Data analysis methods used include simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing. The results of the study indicate that After Sales Service has a significant influence on customer satisfaction with a calculated t value > t table, namely 8.000 > 1.988 and a significance value <0.05, namely 0.001, the results of the partial determination test obtained an R Square (R) value of 0.783 = 78.3%, it can be concluded that the influence of the After Sales Service variable (X1) on Customer Satisfaction (Y) is 78.3% while the remaining 21.7% is influenced by other factors outside the research variables studied. Based on the results of the simple linear regression test, the equation Y = 0.891 + 1.067X1 was found, which means the regression coefficient value is 1.067. It can be concluded that if every 1 unit is added for after sales service (X1), it will increase customer satisfaction (Y) by 1.067. Customer experience is also proven to have a significant effect on customer satisfaction with a calculated value of t> ttable, namely 2.946> 1.988 and a significance value of <0.05, namely 0.004. The results of the partial determination test obtained an R Square (R) value of 0.654 = 65.4%, so it can be concluded that the influence of the Customer Experience variable (X2) on Customer Satisfaction (Y) is 56.6% while the remaining 34.6% is influenced by other factors outside the research variables studied. Based on the results of the simple linear regression test, the equation Y = -10.911 + 1.219X2 was found, which means the regression coefficient value is 1.219. It can be concluded that if every 1 unit is added to customer experience (X2), it will increase customer satisfaction (Y) by 1.219. Simultaneously, the two independent variables have a positive and significant effect on customer satisfaction, with the value of f count > f table, namely 172.012 > 3.10 with a significance value of 0.001 <0.05 and the Adjust R Square (R2) value of 0.799 = 79.9%, then the After Sales Service and Customer Experience variables affect the Customer Satisfaction variable by 79.9% while the remaining 20.1% is influenced by other variables outside this study. It was found that the multiple linear regression model Y = -4.949 + 0.819 X1 + 0.377 X2, the value of After Sales Service (X1) and Customer Experience (X2) showed positive results, which means there is a positive influence between After Sales Service (X1) and Customer Experience (X2) on Customer Satisfaction (Y). If After Sales Service (X1) and Customer Experience (X2) are 0 or do not increase, then Customer Satisfaction (Y) will remain at -4.949